2021
DOI: 10.1038/s41598-021-96088-y
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of predictive factors for lymph node metastasis in superficial esophageal squamous cell carcinoma

Abstract: This study aimed to identify the risk factors of lymph node metastasis (LNM) in superficial esophageal squamous cell carcinoma and use these factors to establish a prediction model. We retrospectively analyzed the data from training set (n = 280) and validation set (n = 240) underwent radical esophagectomy between March 2005 and April 2018. Our results of univariate and multivariate analyses showed that tumor size, tumor invasion depth, tumor differentiation and lymphovascular invasion were significantly corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
3
10
0
Order By: Relevance
“…Our study also found that lesion size > 20 mm, submucosal invasion, and LVI were independent risk factors for LNM, which is consistent with the findings of Ruan et al, [32] Jiang et al [33] and Xu et al [34] Taking the tumor size ≤ 20 mm as a reference, the odds ratio of tumor size > 20 mm was 6.956 (95% CI 1.244–38.913) for predicting LNM, indicating that the lesion size is an important risk factor for LNM. The reason for the large 95% confidence interval may be the small size of the data; however, it still showed that there was a strong relevance between lesion size and LNM.…”
Section: Discussionsupporting
confidence: 93%
“…Our study also found that lesion size > 20 mm, submucosal invasion, and LVI were independent risk factors for LNM, which is consistent with the findings of Ruan et al, [32] Jiang et al [33] and Xu et al [34] Taking the tumor size ≤ 20 mm as a reference, the odds ratio of tumor size > 20 mm was 6.956 (95% CI 1.244–38.913) for predicting LNM, indicating that the lesion size is an important risk factor for LNM. The reason for the large 95% confidence interval may be the small size of the data; however, it still showed that there was a strong relevance between lesion size and LNM.…”
Section: Discussionsupporting
confidence: 93%
“…For example, a retrospective analysis in patients with esophageal squamous cell carcinoma found that tumor size, depth of tumor invasion, degree of tumor differentiation, and lymphovascular invasion were significantly predictors of lymph node metastasis (LNM). 46 These findings were consistent with the present results, which suggested that patients with well-differentiated pathology on the nomogram had lower scores and a better prognosis. Therefore, the early pathological diagnosis of esophageal cancer patients is important in evaluating patient prognosis.…”
Section: Discussionsupporting
confidence: 93%
“…It is worth noting that 15.71% (22/140) of patients had angiolymphatic invasions. Previous studies have demonstrated that angiolymphatic invasion is closely correlated with lymph node metastasis [ 30 , 31 , 32 , 33 ]. A relevant study showed that angiolymphatic invasion may occur even in stage T1a SESCN, with an incidence of approximately 3.12% [ 34 ], which was close to our results (4.29%).…”
Section: Discussionmentioning
confidence: 99%